The Marulić news: what have we learned about a Croatian classic over the last dozen years - Jovanović, Neven (2009)
New discoveries on Marko Marulić and his Latin opus in the last 15 years (unknown works, contribution to the Codex Traguriensis, digitisation of his works and books).
Projekt MZOS
ENG